DETERMINATION OF HEAVY METALS ACCUMULATION IN LACTUCA SATIVA AND SPINACIA OLERACEA GROWN FROM CONTAMINATED SOILS OBTAINED BESIDE FCE KATSINA, NIGERIA - Abdussalam, A. M.; Kabir, M. G.; Nura, S. G. (FUDMA JOURNAL OF SCIENCES, 2021)
The study was carried out to evaluate the heavy metals accumulation in the stems, leaves and roots of Lactuca sativa (Lettuce) and Spinacia oleracea (Spinach). Pot experiment was conducted to examine the phytoextraction ability of these plants for some heavy metals (Cd, Cu, Fe, Pb and Zn) in contaminated soils obtained from an area where indiscriminate burning of waste materials is being carried out beside FCE Katsina. Atomic Absorption Spectrophotometer (AAS) was used for the determination of heavy metals concentrations. The mean levels of metals accumulation evaluated in Lactuca sativa show a higher amount of Fe (47.97 mg/kg) with the lowest amount of Pb (0.44 mg/kg) which follows the order Fe>Zn>Cu>Cd>Pb. Similarly, Spinacia oleracea followed the trend where higher amount of Fe (24.13 mg/kg) with lower Cd (0.25 mg/kg) content was detected, which follows Fe>Zn>Cu>Pb>Cd. The bioaccumulation factor (BAF) was